2010
DOI: 10.1002/polb.21941
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/silver nanoparticles composite: Molecular relaxations investigation by dynamic mechanical analysis and impedance spectroscopy

Abstract: By impedance spectroscopy, Gonzalez‐Campos et al. J Polym Sci Part B: Polym Phys 2009, 47, 932–943, reported the first evidence of a glass transition in a polysaccharide. To gain a better understanding on the molecular relaxations in polysaccharides, we study composites of chitosan (CS)/silver nanoparticles (AgnP) films by dynamic mechanical analysis (DMA) and dielectric spectroscopy in the 2–250 °C temperature range. CS/AgnP films conductivity increases in two orders of magnitude in comparison with pristine C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
(64 reference statements)
7
22
1
Order By: Relevance
“…The direct‐current conductivity (σ dc ) behavior of the PVA films was analyzed by DS with the methodology that we described previously 29–31. Resistance ( R dc ) was obtained from the intersection of the semicircle and the real‐part axis on the impedance plane ( Z ″ = 0), as shown in the inset of Figure 1(a); hence, σ dc could be calculated by the following relationship: where d is the thickness and A is the area of the PVA film, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The direct‐current conductivity (σ dc ) behavior of the PVA films was analyzed by DS with the methodology that we described previously 29–31. Resistance ( R dc ) was obtained from the intersection of the semicircle and the real‐part axis on the impedance plane ( Z ″ = 0), as shown in the inset of Figure 1(a); hence, σ dc could be calculated by the following relationship: where d is the thickness and A is the area of the PVA film, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7a shows the plots of the DC electrical conductivity obtained from impedance measurements as a function of the AgNP and Ag ions wt. % in dry films at room temperature [55]. At low concentration of AgNP and Ag + ions, a decreasing in CS/Ag + ion (silver acetate) composite films exhibited higher conductivity (approximately one order of magnitude) compared with CS/AgnP's composite films with the same Ag content ( Figure 7b).…”
Section: Conductivity Measurementsmentioning
confidence: 87%
“…Neat chitosan exhibits low ionic conductivity that can be related to the presence of small concentration of conductive species in the form of OH + and H + ions [55]. At ambient conditions, film's water content is ca.…”
Section: Conductivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of the peak at 810 cm −1 , attributable to out‐of‐plane PAA OH vibration, marginally increased, and peak broadening due to silver nanoparticle addition was observed. This may be attributable to the interaction of silver nanoparticles with the PVA OH groups and the PAA COOH groups and the formation of hydrogen bonds . The increased intensity and broadening of peaks at 1390 and 1260 cm −1 was assigned to the symmetric and antisymmetric stretches of the COO − groups and it revealed that PAA molecules were adsorbed on the surface of silver nanoparticles through the bidentate band .…”
Section: Resultsmentioning
confidence: 94%